Differences in respiratory mechanics estimation with respect to manoeuvres and mathematical models. (3rd February 2017) - Kretschmer, J; Bibiano, C; Laufer, B; Docherty, P D; Chiew, Y S; Redmond, D; Chase, J G; Möller, K
Abstract: The aim of mechanical ventilation (MV) is to provide sufficient breathing support for critically ill patients with respiratory failure in the intensive care unit (ICU). However, the application of inappropriate MV settings can result in ventilator induced lung injury (VILI) and exacerbate respiratory dysfunction. To prevent VILI, respiratory mechanics properties such as elastance and resistance can be estimated at the bedside to guide MV settings. Different models or methods provide different information and have unique advantages and disadvantages. In this study, the respiratory mechanics of 25 respiratory failure patients were determined using the first order model (FOM) and a viscoelastic model (VEM). The patients underwent different respiratory manoeuvres and their identified respiratory mechanics using these models are studied and compared with a standard clinical method in estimating respiratory mechanics. The results show that both models were able to capture patient-specific mechanics and responses. The FOM was able to provide higher correlation to the standard clinical method while the VEM provides a physiologically more plausible representation.